VALIDITY OF LAND RENTAL AGREEMENTS BETWEEN FOREIGN CITIZENS AND INDONESIAN CITIZENS WITH A TERM OF OVER 80 YEARS IN SUPREME COURT DECISION NUMBER 2785 K/PDT/2011 - Shania Lorusso; Lego Karjoko; Rachma Indriyani (PT. Radja Intercontinental Publishing, 2026)
This study examines the validity of land lease agreements with very long terms, even exceeding 80 years, between foreign nationals and Indonesian citizens as reflected in Supreme Court Decision Number 2785 K/Pdt/2011. The analysis focuses on how the principles of freedom of contract, the principle of justice, and the principle of legal certainty are applied when the structure of the lease clause substantively shifts the nature of the lease into long-term land ownership that resembles a disguised transfer of ownership rights. The study uses a normative juridical method with a statutory regulatory approach and a conceptual approach to the Civil Code, the Basic Agrarian Law, and the doctrine of contract law, which are then linked to the legal considerations of the Supreme Court in the case. The results of the study indicate that unreasonable lease terms, disproportionate rental prices, and unequal bargaining positions give rise to violations of the social function of land and the limits of legal propriety, while also emphasizing the importance of the role of notaries in preventing the emergence of exploitative contract clauses.